Effects of self-healing biomimetic subsoiler on tillage resistance, wear-corrosion performance and soil disturbance morphology under different soil types - Wang, Yueming; Lu, Chenjie; Chen, Jing; Cui, Chenhuan; Pan, Yijie; Pfleging, Wilhelm; Sun, Jiyu (International Journal of Agricultural and Biological Engineering, 2023)
Subsoiling has been widely used all over the world as an important operation method of no-tillage farming. For energy-saving and life-extension, the tillage resistance and wear-corrosion of subsoilers have attracted wide attention. In this study, the tillage resistance, soil disturbance, wear and corrosion of subsoiler with S-T-SK-2# biomimetic structures (S means subsoiler; T means tine; SK means shank; 2#, h/s=0.57, h=5 mm and α=45°.) and self-healing coating under two seasons, two locations with different soil properties (black loam and clay soil) and subsoiling speeds (2 km/h and 3.6 km/h) were investigated. The soil moisture content and compactness affected the tillage resistance and wear-corrosion. The tillage resistance and degree of corrosion on all subsoilers were much larger in clay soil than that in black loam soil. Compared with S-T-SK-2#, the tillage reduction rate of C-S-T-SK-2# (S-T-SK-2# with self-healing coating) was up to 14.32% in clay soil under the speed of 2 km/h. The significance tests of regression equation results showed that subsoiler type and soil properties had a significant impact on soil disturbance coefficient, swelling of total soil layer, bulkiness of the plough pan. It is of a guiding significance for the analysis of soil disturbance. Synergism mechanism of subsoiler coupling with biomimetic structures and self-healing coating was analyzed in following. It depicted the guiding effect of biomimetic structure and the shield function of self-healing coating, resulting in anticorrosion and wear resistance of subsoiler. Keywords: soil types, tillage resistance, wear-corrosion, soil disturbance, self-healing DOI: 10.25165/j.ijabe.20231603.7876 Citation: Wang Y M, Lu C J, Chen J, Cui C H, Pan Y J, Pfleging W, et al. Effects of self-healing biomimetic subsoiler on tillage resistance, wear-corrosion performance and soil disturbance morphology under different soil types. Int J Agric & Biol Eng, 2023; 16(3): 7–14.